ERROR ANALYSIS OF SIMPLE PRESENT TENSE USE IN DESCRIPTIVE TEXT WRITING AT SMA SWASTA MASEHI GBKP BERASTAGI - Purba, Twinta; Sinaga, Elisabeth Ruthana Lasmaria; Lubis, Frida Dian Handini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to identify, classify, and describe the types and patterns of errors in the use of the simple present tense in descriptive texts written by tenth-grade students at SMA Swasta Masehi GBKP Berastagi, along with the underlying causes. A qualitative descriptive design was employed. Thirty students participated by writing descriptive paragraphs about a person and completing a questionnaire. Error analysis based on James and Tono's taxonomy revealed that omission errors, particularly the absence of the "-s/-es" suffix for third-person singular subjects and the linking verb "to be," were the most frequent. Misinformation errors involving incorrect verb forms and confusion between verbs and adjectives were also prevalent. Addition and misordering errors occurred less frequently. Questionnaire responses indicated that first language interference, difficulty distinguishing parts of speech, and limited writing practice contributed significantly to these errors. The findings suggest that pedagogical interventions should address contrastive analysis between Indonesian and English grammar and strengthen students' foundational understanding of verb identification